Influence of grease formulation on thrust bearings power loss - Cousseau, Tiago (2014)
The minimization of the power loss and the use of the biodegradable greases have attracting considerable attention. To compare the energetic performance of biodegradable lubricant greases, power loss tests were performed on a modified four-ball machine. A correlation between the grease formulation and rheology was established with its energetic performance